Pengaruh Religiusitas dan Faktor Lainnya terhadap Intensi Pembelian: Studi Empiris Kosmestik Safi di Tangerang - Dihin Septyanto; Swastika Fadila Santi (Jurnal Multidisiplin Borobudur, 2023)
This study aims to determine and prove the effect of religiosity and other factors such as subjective norms, perceptions of behavioral control on purchase intentions through halal awareness as intervening variables on Safi cosmetics in Tangerang. The population in this study were visitors at Purimall Karawaci, Tangerang Regency, who used cosmetic products from Safi. Collecting data using a questionnaire with a purposive sampling method of 140 respondents. Analysis of the data used in this study using path analysis or path analysis. The results of the study show that religiosity and other factors such as subjective norms and perceptions of behavioral control influence halal awareness. As for the religiosity factor, perceived behavioral control, subjective norms, and also halal awareness have a direct effect on purchase intentions. However, the direct effect of religiosity, subjective norms, and perceived behavioral control has a greater effect than the indirect effect, so this shows that the halal awareness factor does not have a stronger effect as an intervening variable.